2D V2O5 nanoflakes as a binder-free electrode material for high-performance pseudocapacitor. Issue 17 (1st September 2021) - Javed, Muhammad Sufyan; Najim, Tayyba; Hussain, Iftikhar; Batool, Saima; Idrees, Muhammd; Mehmood, Ayaz; Imran, Mohammed; Assiri, Mohammad A.; Ahmad, Awais; Ahmad Shah, Syed Shoaib
Abstract: Two-dimensional (2D) nanoflakes of vanadium pentoxide (V2 O5 ) are directly developed on the titanium (Ti) substrate (VO@Ti) as an innovative electrode for pseudocapacitor. The designed VO@Ti electrode offers impressive capacitance of 1520 Fg -1 at 1.5 Ag -1 and superb long-term reliability with a 99% retention over 12000 cycles at 20 Ag -1 based on the merits of highly exposed active sites and improved electrical conductivity. Graphical abstract: The designed VO@Ti electrode offers high capacitive type charge storage based on the merits of highly exposed active sites and improved electrical conductivity. Image 1 Highlights: 2D-morphology based novel V2 O5 nanobelts as an electrode material for supercapacitor is developed. Binder-free VO@Ti electrode exhibits exceptional high charge storage performance 1520 at F g -1 at 1.5 A g -1 . The VO@Ti electrode exhibited high capacitance retention of 99% after 12000 cycles. The VO@Ti electrode stored highly capacitive type charge at low scan rates.